Cytotoxicity studies of curcumin loaded-cockle shell-derived calcium carbonate nanoparticles - Muhammad, Mailafiya Maryam; Mohd Moklas, Mohamad Aris; Abubakar, Kabeer; Danmaigoro, Abubakar; Chiroma, Samaila Musa; Abdul Rahim, Ezamin; Abu Bakar Zakaria, Md Zuki (Bentham Science Publishers, 2021)
Background: Cockle shell-derived calcium carbonate nanoparticles (CSCaCO3NP) are natural biogenic inorganic material that is used in drug delivery mainly as a bone-remodeling agent as well as a delivery agent for various therapeutics against bone diseases. Curcumin possesses a wide safety margin and yet puzzled with the problem of poor bioavailability due to insolubility. Propounding in vitro and in vivo studies on toxicity assessments of newly synthesized nanoparticles are ongoing to overcome some crucial challenges regarding their safety administration. Nanotoxicology has paved ways for concise test protocols to monitor sequential events with regards to possible toxicity of newly synthesized nanomaterials. The development of nanoparticle with no or less toxic effect has gained tremendous attention. Objective: This study aimed at evaluating the in vitro cytotoxic effect of curcumin-loaded cockle shell-derived calcium carbonate nanoparticles (Cur-CSCaCO3NP) and assessing its biocompatibility on normal cells using standard techniques of WST’s assay. Methods: Standard techniques of WST’s assay was used for the evaluation of the biocompatibility and cytotoxicity. Results: The result showed that CSCaCO3NP and Cur-CSCaCO3NP possess minimal toxicity and high biocompatibility on normal cells even at a higher dose of 500 μg/ml and 40 μg/ml, respectively. Conclusion: CSCaCO3NP can be termed an excellent non-toxic nanocarrier for curcumin delivery. Hence, curcumin loaded cockle shell derived calcium carbonate nanoparticles (Cur-CSCaCO3NP) could further be assessed for various in vivo and in vitro therapeutic applications against various bone- related ailments.